2022
DOI: 10.18433/jpps32715
|View full text |Cite
|
Sign up to set email alerts
|

Health Canada Usage of Real World Evidence (RWE) in Regulatory Decision Making compared with FDA/EMA usage based on publicly available information

Abstract: Purpose: Between January 2020 and December 2021, Health Canada provided a Summary Basis of Decision (SBD) for each of 110 products approved, including 29 oncology products and 21 non-oncology orphan drugs. This review sought to gain insight into how Real Word Evidence (RWE) impacts regulatory decision making. Methods: SBDs for oncology drugs and non-oncology orphan drugs were reviewed for evidence of use of the RWE or historical data to support regulatory decisions. This information was compared with both FDA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 8 publications
(14 reference statements)
0
15
0
Order By: Relevance
“…Health Canada Summary Basis of Decision (SBD) database: Health Canada’s database containing summary reviews of all approvals from January 2019 to December 2021 was used as the anchor database [ 20 ] for all products studied in this review article. The review of the SBD database was performed as described previously [ 8 ]. Briefly, the database from 2019–2021 was downloaded into an Excel spreadsheet for abstraction.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Health Canada Summary Basis of Decision (SBD) database: Health Canada’s database containing summary reviews of all approvals from January 2019 to December 2021 was used as the anchor database [ 20 ] for all products studied in this review article. The review of the SBD database was performed as described previously [ 8 ]. Briefly, the database from 2019–2021 was downloaded into an Excel spreadsheet for abstraction.…”
Section: Methodsmentioning
confidence: 99%
“…Despite these promising public announcements, a recent publication suggested that Health Canada’s usage of RWE in recent regulatory decision making was low when compared with the usage by the U.S. Food and Drug Administration (FDA) and the European Medicines Agency (EMA) in oncology and orphan drugs. However, an increase in RWE use was observed in Notice of Compliance with Conditions (NOCc) reviews [ 8 ]. The study showed that the majority of conditional approvals were granted to oncology drugs due to the life-threatening and severe nature of these diseases.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Randomized controlled trials (RCTs) are the primary source of evidence for regulatory and health technology assessment (HTA) decision-making (1). However, there has been increasing consideration of real-world data (RWD) and realworld evidence (RWE) in the regulatory/HTA decision-making process to complement RCTs and address evidence gaps (2)(3)(4)(5). For instance, a retrospective analysis of single-arm HTA submissions reported that the proportion of submissions that included RWD-based external control arms (ECAs) increased 22% per year over 2015-2019 (6).…”
Section: Introductionmentioning
confidence: 99%